17β-estradiol and methylprednisolone association as a therapeutic option to modulate lung inflammation in brain-dead female rats - Vidal-dos-Santos, Marina; Anunciação, Lucas F.; Armstrong-Jr, Roberto; Ricardo-da-Silva, Fernanda Y.; Ramos, Isabella Yumi Taira; Correia, Cristiano J.; Moreira, Luiz F. P.; Leuvenink, Henri G. D.; Breithaupt-Faloppa, Ana C. (Frontiers in Immunology, 2024)
Brain death (BD) is known to compromise graft quality by causing hemodynamic, metabolic, and hormonal changes. The abrupt reduction of female sex hormones after BD was associated with increased lung inflammation. The use of both corticoids and estradiol independently has presented positive results in modulating BD-induced inflammatory response. However, studies have shown that for females the presence of both estrogen and corticoids is necessary to ensure adequate immune response. In that sense, this study aims to investigate how the association of methylprednisolone (MP) and estradiol (E2) could modulate the lung inflammation triggered by BD in female rats. Female Wistar rats (8 weeks) were divided into four groups: sham (animals submitted to the surgical process, without induction of BD), BD (animals submitted to BD), MP/E2 (animals submitted to BD that received MP and E2 treatment 3h after BD induction) and MP (animals submitted to BD that received MP treatment 3h after BD induction). Hemodynamics, systemic and local quantification of IL-6, IL-1β, VEGF, and TNF-α, leukocyte infiltration to the lung parenchyma and airways, and adhesion molecule expression were analyzed. After treatment, MP/E2 association was able to reinstate mean arterial pressure to levels close to Sham animals (p<0.05). BD increased leukocyte infiltration to the airways and MP/E2 was able to reduce the number of cells (p=0.0139). Also, the associated treatment modulated the vasculature by reducing the expression of VEGF (p=0.0616) and maintaining eNOS levels (p=0.004) in lung tissue. Data presented in this study show that the association between corticoids and estradiol could represent a better treatment strategy for lung inflammation in the female BD donor by presenting a positive effect in the hemodynamic management of the donor, as well as by reducing infiltrated leukocyte to the airways and release of inflammatory markers in the short and long term.